Pluralism and the less powerful: accommodating multiple interests in local forest management. (1st January 2001) - Wollenberg, Eva; Anderson, Jon; Edmunds, David
Forest decision-making is becoming more pluralistic. As the numbers of groups involved in forest decisions have increased, concern about how to accommodate multiple interests has similarly burgeoned. In this article we present pluralism as a foundation for understanding how less powerful groups' interests can be accommodated. We examine approaches to how interests are defined, communicated and coordinated to review the scope of possibilities for improving pluralism. Experience with these methods suggests that accommodation that genuinely reflects the interests of disadvantaged groups is most likely to occur where state and civil society governance institutions provide opportunities for 1) mutual learning among interest groups, 2) iterative cycles of bounded conflict and co-operation, 3) public, transparent decision-making, 4) checks and balances in decision-making among groups and 5) the provision of capacity building or political alliances for disadvantaged interest groups. High transaction costs, persistent injustices and impossibility of neutral facilitation pose contradictions to the possibilities of achieving accommodation and need to be recognised and negotiated.